Clinical and Cytology Description of Various Neck Lumps in Madani Medan Hospital - Rido Aliberto Sitanggang; Juliana Lina (HM Publisher, 2021)
This study aims to determine the clinical and cytological features of various neck lumps. This study used a descriptive observational method with a cross-sectional approach to determine the clinical and cytological features of various neck lumps. This study used secondary data from patients with indications of a neck lump who were undergoing treatment or examination at the Medan Madani Hospital in 2018 - 2019. The population in this study were all patients with symptoms and positives experiencing a lump in the neck, at Madani Hospital Medan. Data processing is carried out after the observation and recording of medical record data is in accordance with what is needed, the data obtained are tabulated and coded for later analysis. The results of this study indicated that respondents who experienced thyroid nodules were more dominant in female respondents with a total of 11 respondents, with the most common type of thyroid nodule adenoma follicular thyroid, namely 9 respondents of the female gender. Respondents who experienced inflammation were dominated by female respondents with a non-specific chronic inflammation process on the right side of the neck with a total of 10 respondents with a percentage of 23.8%.